The historical development of Latvian aviation and airfield territories - Markova, Madara; Stola, Diāna (Landscape Architecture and Art, 2023)
In the 20th century, built airfields and airports, have significantly impacted the European landscape and environmental quality today. Territories that have lost their former function can now be considered as a stimulus for the creation of new landscapes and for urban development. The publication covers the history of Latvian aviation through time, where a total of 97 airfields have been established, which served as military, agricultural, sports, and civil aviation airfields. Scientific literature, popular scientific literature were used to gather information. For mapping was used ArcGIS. Nowadays, according to the data of the Civil Aviation Agency, 9 airfields are certified – 7 civil aviation airfields, and 2 air transportation airfields. As well as a military base of the Air Force has been established at Lielvārde airfield. Airfield’s development opportunities until now have not been researched in Latvia, this is the first study to capture resources available and development strategies.